STUDY REGARDING LEARNING THE FOOTBALL GAME TECHNICAL PROCEDURES AT PRIMARY STUDENTS - Vasile Septimiu ORMENIȘAN; Dan MONEA; Sergiu POP; Cosmin MOCA; Cristina Ionela ORMENIȘAN; Mihai Alexandru TURCU (Studia Universitatis Babeş-Bolyai: Educatio Artis Gymnasticae, 2023)
In the methodology of sports games, it is stipulated that the teaching of any technical procedure is based on some models, these models as the result of many biomechanical studies that refer not only to the main procedure, but also to all details specific to different styles. Hypothesis. In the case of some primary school students, are increase of their technical level, can be motived. This has been possible because the methods are carefully selected and suitable for their age. Methods and means. The subjects of this research are students from Elementary School, Gâlgăul Almașului, Sălaj County, the research lasts from 2021-2022. 15 students has been involved: 9 from the third form and 6 from the 4th. At the beginning of the study, their technical abilities have been tested: kicking-precision frequency, the ability of keeping the ball in the air as much as possible, dribbling through obstacles. Data processing used statistical tests like: accepted standard deviation, variability coefficient, the T test. Results. The frequency of kicking precision the 3 rd form – 7.11 – (T.I) executions and 8.44 (T.F) executions, all the 4th form 7.50 T.I executions and 9.66 executions T.F. Conclusions. The results obtained shows that the selected methods lead to the technical improvement of in football game. A key factor represents a well knowing of the students’ training level and the methodology.